2009
DOI: 10.1179/174328409x405625
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum brazing of NiTi alloy by AgCu eutectic filler

Abstract: Joining of NiTi alloy to itself has been realised by vacuum brazing process using AgCu28 eutectic as filler metal. Microstructures, mechanical and shape memory behaviour have been investigated. The shearing strength of the brazed joint exceeds 100 MPa, and rupture occurs at the diffusion layer of parent metal beside brazing metal. The brazed joint will be stronger than parent metal on condition of the specimen with a joint of lap length 10 times of plate thickness. The brazed specimen shows a good shape memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…With both of these alloys joining was achieved with a significant difference of the existing phases after the brazing process. Ag-Cu alloy was used for vacuum furnace brazing of NiTi by Zhao et al [101]. Lap joints were prepared and it was observed that after a given lap length the strength of the brazed joint was higher than that of the base material.…”
Section: Brazing and Solderingmentioning
confidence: 99%
See 1 more Smart Citation
“…With both of these alloys joining was achieved with a significant difference of the existing phases after the brazing process. Ag-Cu alloy was used for vacuum furnace brazing of NiTi by Zhao et al [101]. Lap joints were prepared and it was observed that after a given lap length the strength of the brazed joint was higher than that of the base material.…”
Section: Brazing and Solderingmentioning
confidence: 99%
“…Several works have addressed the influence of Ag-based filler materials on the joint characteristics of NiTi/NiTi brazed joints [99][100][101]. Different fillers and heating methods were tested.…”
Section: Brazing and Solderingmentioning
confidence: 99%
“…Ag-Cu eutectic, Ag-Cu-Ti and Ag-Ti llers have been applied in brazing Ti 50 Ni 50 SMA, and the brazed joints demonstrate acceptable joint strengths of above 100 MPa. 6,7) However, dissimilar brazing Ti 50 Ni 50 SMA is seldom studied in literature. 8) Gold-based ller metals have been used to braze iron-, nickel-and cobalt-based alloys where oxidation and/ or corrosion resistance is required.…”
Section: Introductionmentioning
confidence: 99%